One-year outcomes following implantation of second-generation trabecular micro-bypass stents in conjunction with cataract surgery for various types of glaucoma or ocular hypertension: multicenter, multi-surgeon study - Clement CI (Dove Medical Press, 2019)
Colin I Clement,1–4 Frank Howes,5 Alexandros S Ioannidis,6 Michael Shiu,7 David Manning8 1Eye Associates, Sydney, NSW, Australia; 2Fairfield Eye Surgery, Fairfield, NSW, Australia; 3Glaucoma Unit, Sydney Eye Hospital, Sydney, NSW, Australia; 4Discipline of Ophthalmology, The University of Sydney, Sydney, NSW, Australia; 5Eye & Laser Centre Gold Coast, Southport, QLD, Australia; 6Vision Eye Institute, Melbourne, VIC, Australia; 7Laser Sight Laser Cataract & Lens Specialists, Sydney, NSW, Australia; 8Hunter Cataract & Eye Centre, Sydney, NSW, Australia Purpose: To assess the utility and safety of implanting two second-generation trabecular micro-bypass stents following cataract surgery in eyes with mild to advanced glaucoma or ocular hypertension (OHT). Patients and methods: Retrospective study of iStent®inject trabecular micro-bypass implantation with cataract surgery by five surgeons at five sites in Australia. Eyes had mild to advanced glaucoma (predominantly primary open-angle, appositional angle-closure, or pseudoexfoliative glaucoma) or OHT and cataract requiring surgery. Effectiveness measures included intraocular pressure (IOP); medication burden; and proportions of eyes with no medications, ≥2 medications, stable or decreased medications vs preoperative, and IOP ≤18 mmHg. Safety measures included visual acuity, cup-to-disc ratio (CDR), visual field (VF), complications, adverse events, and secondary surgical interventions. Patients have been followed for 12 months, and follow-up is ongoing. Results: Of the 290 total eyes that underwent surgery, 165 eyes had 12-month outcomes at the time of data collection and are included in this report. In these eyes, mean Month 12 IOP reduced by 23.2% from 18.27±5.41 mmHg preoperatively to 14.04±2.98 mmHg (P<0.001), with 95.8% of eyes achieving Month 12 IOP of ≤18 mmHg vs 60.6% preoperatively. Mean number of medications at 12 months decreased by 71.5%, 0.47±0.95 vs 1.65±1.28 preoperatively; 76.4% of eyes were on zero medications vs 17.6% preoperatively (P<0.001); 14.5% of eyes were on ≥2 medications vs 46.7% preoperatively (P<0.001); and 98.2% of eyes maintained or reduced medications vs their preoperative regimen. Favorable safety included no stent-related intraoperative complications; limited and transient postoperative adverse events; and stable CDR, VF, and visual acuity. Three eyes with more advanced disease underwent additional glaucoma surgeries. Conclusion: iStent inject implantation with cataract surgery significantly and safely reduced medications and IOP in eyes with various types and severities of glaucoma within a multicenter, multi-provider, real-life setting. Keywords: microinvasive glaucoma surgery, MIGS, glaucoma, iStent inject, intraocular pressure, second-generation, medication, safety